Impacts of COVID-19 on family violence in Thailand: prevalence and influencing factors - Wilai Napa; Nareemarn Neelapaichit; Ronachai Kongsakon; Somporn Chotivitayataragorn; Umaporn Udomsubpayakul (BMC, 2023)
Abstract Background The COVID-19 pandemic drastically affected societies globally, prompting rising unemployment, insufficient household incomes, and stress and undermining women's and children's health within families. This study examined family violence and identified influencing factors during the COVID-19 pandemic in Thailand. Methods A mixed-method design was used, entailing a questionnaire followed by focus group interviews. A cross-sectional survey was administered to investigate family violence among 1285 female respondents aged 15 years and above who were recruited through stratified sampling. The Cronbach alpha and and inter-raters Kappa coefficient values for the questionnaire were 0.67 and 1.00, respectively. In addition, a descriptive qualitative instrument was employed to analyze the data sets from four focus group interviews held with 32 staff members from agencies that deal with family violence. The researchers jointly developed the focus group questions, which focused on the impacts of the COVID-19 pandemic on family violence. They independently analyzed data using content analysis. Results The majority of the study participants were aged above 45 years (>50%), married (61.1%), lived in single-family settings (52.5%), had lost their jobs (64.4%), and had economic constraints that were moderate (37.8%) to severe (40.6%). The prevalence of family violence, which was primarily physical, was 42.2%. Family income, stress, and substance abuse were the main factors associated with family violence. These findings were correlated with those from the qualitative interviews. Conclusions The COVID-19 pandemic had indirect impacts through family violence. Women were subjected to family violence behaviors, which were associated with household income, economic status, stress, and substance abuse. These behaviors included psychological and physical violence, as well as sexual abuse. Future interventions should focus on financial support and stress reduction.